METHODS OF DEVELOPING DIDACTIC GAMES IN PRESCHOOL EDUCATION ORGANIZATIONS AND THEIR PEDAGOGICAL EFFECTIVENESS - DJumayeva Zarnigor Aloxiddinova qizi (International Journal of Literature and Language Studies, 2026)
This article systematically investigates the scientific-theoretical foundations, modern methodical approaches, and pedagogical effectiveness of developing didactic games in preschool education organizations. Nowadays, the excessive academization of the educational process and the alienation from game technologies, which constitute the leading activity of preschool children, are analyzed as a pressing pedagogical contradiction. Within the framework of the study, traditional educational methods (frontal explanation and demonstration) were compared experimentally with the author's developed "Systemic Didactic Games Model," which integrates object-sensory, verbal-logical, and intellectual-board games. A total of 50 children from senior and preparatory groups (25 in the control group and 25 in the experimental group) participated in the experiment. Children's cognitive, linguistic, and socio-emotional development levels were monitored over 6 months based on J. Piaget and Wechsler methodologies. Mathematical-statistical and pedagogical diagnostics indicated that in the experimental group where the systemic didactic games model was implemented, children's logical thinking increased by 32% (from 44% to 76%), vocabulary and speech activity by 32% (from 52% to 84%), and teamwork and social adaptation skills by 32% (from 48% to 80%) compared to the control group. Most importantly, game technologies accelerated the learning pace of educational tasks by 1.5 times while reducing psychophysical tension and fatigue by 40%. The article scientifically substantiates the four-component mechanism of didactic games (goal, rule, action, outcome) and the educator's role as a facilitator. The findings of the study serve as a practical foundation for developing methodical recommendations for preschool educators, methodologists, and curriculum designers.